Preparation method and application of magnetic composite transition bimetallic oxide catalyst
By introducing other transition metals into the magnetic transition bimetal oxide catalyst, the lattice distortion is solved, and the problem of insufficient yield and selectivity of existing catalysts in lignite cracking is achieved, and a high-efficiency and low-energy consumption lignite cracking process is achieved.
Patent Information
- Application Number
- CN202411243701.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-02-07
AI Technical Summary
During the lignite cracking process, it is difficult for existing catalysts to improve the yield of soluble components and the selectivity of aromatic hydrocarbons, and the process is complex and the energy consumption is high.
By introducing a small amount of other transition metals into the synthesis of magnetic transition bimetal oxide catalysts, the use of doping atoms to cause lattice distortion, providing more active sites, thereby improving the yield of lignite soluble components and the selection of aromatic hydrocarbons sex.
The yield of soluble components and aromatic hydrocarbons during lignite cracking is achieved, the process flow is simplified, energy consumption is reduced, and the activity and selectivity of the catalyst is improved.
Smart Images

Figure CN119386874A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of transition bimetallic oxide catalysts, and in particular, relates to a preparation method and application of a magnetic composite transition bimetallic oxide catalyst. Background Art
[0002] Simple aromatic hydrocarbons (such as benzene, toluene, etc.) are basic raw materials for preparing other high-grade aromatic compounds. At present, most of the simple aromatic hydrocarbons in the world come from petrochemical industry. The main methods for producing simple aromatic hydrocarbons from crude oil are catalytic reforming and steam cracking. Catalytic reforming is to firstly form a large amount of aliphatic hydrocarbons in crude oil into rings and dehydrogenate them into aromatic hydrocarbons by platinum-rhenium catalyst, then separate the aromatic hydrocarbons by extraction, and finally obtain benzene, toluene, etc. by distillation. Steam cracking is to use the characteristics of pyrolysis gasoline, one of the by-products in the process of producing olefins by steam cracking of petroleum components such as naphtha and heavy diesel, which is rich in benzene (40-60%). Proper separation of pyrolysis gasoline can obtain simple aromatic hydrocarbons such as benzene and toluene. In addition, simple aromatic hydrocarbons can also be separated from coal tar produced by coal dry distillation. The process of producing simple aromatic hydrocarbons in petrochemical industry is complex, the reaction conditions are harsh, and the equipment investment is high. The output of coal tar is small and it is often used for catalytic hydrogenation to produce fuel oil. Even if simple aromatic hydrocarbons are obtained by separation, the output is limited. Therefore, it is necessary to open up a new path with simple process, low energy consumption and large-scale production of simple aromatic hydrocarbons.
[0003] Lignite is rich in aromatic rings and heteroatom units, and heteroatom unit fragments are often connected by >CX (X = O, N and S) bridge bonds. Transition metal oxides can effectively activate H2 through oxygen vacancies or metal sites on their surfaces and further induce the cleavage of >CX bridge bonds. The currently used transition metal oxides include Fe2O3, NiO, CuO, MoO x Due to their non-recyclability and fewer active sites, various measures are often taken to increase their specific surface area and catalytic hydrogenation activity, which greatly increases the cost of the catalyst. Although magnetically recyclable transition bimetallic oxides such as NiFe2O4 and CuFe2O4 have good CX bridge bond activity in cracking lignite, and effective control of conditions can also reduce the formation of hydrogenation products and rearrangement products, the yield of soluble components and the selectivity of aromatic hydrocarbons need to be improved.
[0004] Therefore, a catalyst which has good catalytic cracking performance for lignite and can obtain a higher yield of soluble components and a higher selectivity of aromatic hydrocarbon components is urgently needed in the art. Summary of the invention
[0005] In order to solve the above technical problems, the present invention discloses a preparation method and application of a magnetic composite transition bimetallic oxide catalyst. In view of the problems existing in the current magnetic transition bimetallic oxide catalyst, a small amount of other transition metals are introduced into the synthesis thereof. The doped atoms are similar in size to the original lattice atoms and can partially occupy the sites of the original lattice atoms, resulting in changes in the lattice parameters of the magnetic transition bimetallic oxide and causing lattice distortion, thereby providing more active sites and defect sites, improving the yield of soluble components of lignite and the selectivity of aromatic hydrocarbons, and having broad market application prospects.
[0006] Based on the above objectives, the first technical solution of the present application provides a method for preparing a magnetic composite transition bimetallic oxide catalyst, comprising the following steps:
[0007] S1. dissolving cobalt salt, nickel salt and iron salt in a solvent to obtain a mixed solution;
[0008] S2. adding a strong reducing agent to the mixed solution, performing a hydrothermal reaction to crystallize to obtain a suspension;
[0009] S3. Purify the suspension to obtain a magnetic composite transition bimetallic oxide catalyst.
[0010] Preferably, the cobalt salt is at least one of cobalt acetate, cobalt sulfate or cobalt nitrate;
[0011] The nickel salt is at least one of nickel acetate, nickel sulfate or nickel nitrate;
[0012] The iron salt is at least one of ferric nitrate, ferric chloride or ferric acetylacetonate.
[0013] Furthermore, the volume ratio of the amount of the cobalt salt, nickel salt, and iron salt described in S1 to the solvent is: mmol:mmol:mmol:mL=(0.18-0.9):(3.42-2.7):(7.2-10.8):(50-100).
[0014] Preferably, the strong reducing agent is at least one of hydrazine hydrate or sodium borohydride.
[0015] Furthermore, the volume ratio of the strong reducing agent in S2 to the solvent in S1 is (5-20):100.
[0016] Furthermore, the hydrothermal reaction temperature in S2 is 100-200° C., and the reaction time is 10-20 h.
[0017] Furthermore, the purification in S3 is to obtain the composite transition bimetallic oxide catalyst by centrifuging, washing and drying the suspension.
[0018] Furthermore, the centrifugal speed is 4000-6000 rpm, and the centrifugal time is 3-15 min; the drying is vacuum drying, the drying temperature is 60-90° C., and the drying time is 4-20 h.
[0019] And, a magnetic composite transition bimetallic oxide catalyst prepared according to the above preparation method.
[0020] The second technical solution of the present application provides the application of the above-mentioned magnetic composite transition bimetallic oxide in the hydrogenation reaction of lignite and the hydrogenation conversion reaction of lignite-related model compounds.
[0021] The beneficial effect of the present invention is that cobalt salt is added during the reaction process of preparing NiFe2O4 by using nickel salt and iron salt, and CoFe2O4 and NiFe2O4 magnetic composite transition bimetallic oxide (denoted as Co x Ni (1-x) Fe2O4); compared with the prior art, the prepared magnetic composite transition bimetallic oxide catalyst has the following advantages:
[0022] (1) The preparation process of the present invention is simple, the production cycle is short, the safety and stability are high, and no calcination is required. It is green, efficient, and safe to operate.
[0023] (2) The magnetic composite transition bimetallic oxide catalyst prepared by the present invention is in the form of nano-spheres, with uniform particle size and no obvious agglomeration. The cobalt, nickel and iron elements are evenly distributed, and the catalyst has strong acidity and relatively suitable distribution of weak acid sites, medium-strong acid sites and strong acid sites. The catalyst has high catalytic hydrogenation reaction activity and product selectivity, and can efficiently activate H2 to H···H, and further homolytically split into H· and heterolytically split into H - Release H + , in H···H, H· and H + Under the synergistic effect of , it has better catalytic cracking performance on lignite, and is more conducive to the cracking of >CC< bridge bonds and >CX bridge bonds.
[0024] (3) The application of the magnetic composite transition bimetallic oxide catalyst provided by the present invention is to prepare a magnetic composite transition bimetallic oxide catalyst for the hydrocracking of phenyl benzyl ether, which has the characteristics of high conversion rate and high yield of derived aromatics; the present invention prepares Co 0.20 Ni 0.80 Fe2O4 nano-spherical catalyst was used for hydrocracking of Dongming lignite in Inner Mongolia, and the yield of derived solubles increased from 12.23% to 15.37%. Among them, the yield of light components increased by 51.2%, and the yield of heavy components increased by 12.7%. The yield of derived aromatics in light components increased from 43.12% to 52.59%, an increase of 22.0%, while the yield of phenolic substances decreased from 7.24% to 3.28%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Magnetic Co is prepared in Examples 1 to 4 of the present invention. x Ni (1-x) XRD pattern of Fe2O4;
[0026] Figure 2 The magnetic Co prepared in Example 1 of the present invention 0.20 Ni 0.80 SEM images, element distribution maps and H2-TPR images of Fe2O4 and pure NiFe2O4;
[0027] Figure 3 The magnetic Co prepared in Example 1 of the present invention 0.20 Ni 0.80 X-ray photoelectron spectroscopy of Fe2O4;
[0028] Figure 4 The magnetic Co prepared in Example 1 of the present invention 0.20 Ni 0.80 NH3-TPD diagram of Fe2O4;
[0029] Figure 5 The magnetic Co prepared in Example 1 of the present invention 0.20 Ni 0.80 Comparison of the yields of light components, heavy components and coal residues from catalytic hydrocracking and non-catalytic hydrocracking of Dongming lignite from Inner Mongolia using Fe2O4;
[0030] Figure 6 The magnetic Co prepared in Example 1 of the present invention 0.20 Ni 0.80 Distribution diagram of core group components of light components used for catalytic hydrocracking of Dongming lignite from Inner Mongolia using Fe2O4. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The chemical composition of the magnetic composite transition bimetallic oxide prepared in the present application is CoFe2O4 and NiFe2O4. The amount ratio of cobalt salt and nickel salt added is different, so the proportion of CoFe2O4 and NiFe2O4 is also different. x Ni (1-x) Fe2O4 represents a magnetic composite transition bimetallic oxide.
[0033] The complexity of coal structure makes it very difficult to directly study the catalytic hydrogenation process and reaction mechanism of coal. Therefore, this application uses lignite-related model compounds instead of lignite to study the catalytic hydrogenation reaction mechanism. Phenyl benzyl ether, which is similar to lignite structure, is preferred. Phenyl benzyl ether has a simple molecular structure, containing only phenyl and benzyl, and the two are connected by an oxygen atom, which makes it easier to study the catalytic hydrogenation reaction path and mechanism.
[0034] One embodiment of the present application provides a method for preparing a composite transition bimetallic oxide catalyst, comprising the following steps:
[0035] S1. dissolving cobalt salt, nickel salt and iron salt in a solvent to obtain a mixed solution;
[0036] S2. adding a strong reducing agent to the mixed solution, performing a hydrothermal reaction to crystallize to obtain a suspension;
[0037] S3. Purify the suspension to obtain a magnetic composite transition bimetallic oxide catalyst.
[0038] It can be understood that the cobalt salt, nickel salt and iron salt described in this embodiment are all water-soluble metal salts. Therefore, the cobalt salt is preferably at least one of cobalt acetate, cobalt sulfate or cobalt nitrate, the nickel salt is preferably at least one of nickel acetate, nickel sulfate or nickel nitrate, the iron salt is preferably at least one of ferric nitrate, ferric chloride or ferric acetylacetonate, and the solvent is preferably deionized water.
[0039] In a further embodiment, the volume ratio of the amount of cobalt salt, nickel salt, iron salt to the solvent is: mmol:mmol:mmol:mL=(0.18-0.9):(3.42-2.7):(7.2-10.8):(50-100).
[0040] It can be understood that the role of the strong reducing agent of the present application is to undergo a redox reaction with the metal ions, reducing them to metal elements, so that they have better ability to activate hydrogen in the catalytic reaction, thereby improving the catalytic hydrogenation performance. The strong reducing agent of the present application is preferably at least one of hydrazine hydrate or sodium borohydride.
[0041] In a further embodiment, the volume ratio of the strong reducing agent to the solvent in S1 is (5-20):100.
[0042] In this embodiment, the hydrothermal reaction is preferably carried out in a polytetrafluoroethylene-lined hydrothermal reactor, and the pressure of the crystallization reaction system is effectively regulated by changing the volume of the solution added to the reactor or selecting reactors of different capacities, which is conducive to the stable synthesis of the magnetic composite transition bimetallic oxide catalyst. Specifically, the mixed solution is transferred to a polytetrafluoroethylene-lined hydrothermal reactor, a strong reducing agent is added, and then the reactor is sealed and placed in a blast drying oven for hydrothermal crystallization. At this time, the total volume of the mixed solution and the volume of the polytetrafluoroethylene-lined hydrothermal reactor are (45-75): 100 to ensure the smooth progress of the reaction.
[0043] In some preferred embodiments, the hydrothermal reaction temperature is 100-200° C., and the reaction time is 10-20 h.
[0044] In some specific embodiments, the purification in S3 is to obtain a composite transition bimetallic oxide catalyst by centrifuging, washing and drying the suspension; the centrifugal speed is 4000-6000rpm, and the centrifugal time is 3-15min; the drying is vacuum drying, the drying temperature is 60-90°C, and the drying time is 4-20h.
[0045] The preparation method and technical effects of the present application will be described below in conjunction with specific embodiments.
[0046] Example 1
[0047] A method for preparing a magnetic composite transition bimetallic oxide catalyst, the specific process is as follows:
[0048] S1. Add 0.179 g of cobalt acetate tetrahydrate, 0.716 g of nickel acetate tetrahydrate and 2.543 g of ferric acetylacetonate to 70 mL of deionized water, stir with a glass rod at room temperature and dissolve until ready for use;
[0049] S2. The mixed solution obtained in step S1 was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, 5 mL of hydrazine hydrate was added and shaken, and then the reactor was sealed and placed in a 180 ° C forced air drying oven for crystallization for 12 h;
[0050] S3. The hydrothermal reactor in step S2 is taken out of the drying oven, and after being naturally cooled to room temperature, the suspension in the reactor is centrifuged at a centrifugal speed of 5000 rpm for 5 min, and then the solid is alternately washed with deionized water and anhydrous ethanol until it is neutral, and then vacuum dried at 80°C for 4 h to obtain a composite transition bimetallic oxide catalyst (denoted as Co) with a mass distribution of 20% CoFe2O4 and 80% NiFe2O4. 0.20 Ni 0.80 Fe2O4).
[0051] Example 2
[0052] The difference from Example 1 is that the amount of cobalt acetate tetrahydrate added is 0.134 g, and the amount of nickel acetate tetrahydrate added is 0.761 g, so that the theoretical amount distribution of the composite transition bimetallic oxide catalyst (denoted as Co 0.15 Ni 0.85 Fe2O4).
[0053] Example 3
[0054] The difference from Example 1 is that the amount of cobalt acetate tetrahydrate added is 0.090 g, and the amount of nickel acetate tetrahydrate added is 0.806 g, so that a composite transition bimetallic oxide catalyst (denoted as Co) with a theoretical mass distribution of 10% CoFe2O4 and 90% NiFe2O4 can be obtained. 0.10 Ni 0.90 Fe2O4).
[0055] Example 4
[0056] The difference from Example 1 is that the amount of cobalt acetate tetrahydrate added is 0.045 g, and the amount of nickel acetate tetrahydrate added is 0.850 g, so that a composite transition bimetallic oxide catalyst (denoted as Co) with a theoretical mass distribution of 5% CoFe2O4 and 95% NiFe2O4 can be obtained. 0.05 Ni 0.95 Fe2O4).
[0057] Example 5
[0058] The difference from Example 1 is that the amount of cobalt acetate tetrahydrate added is 0.224 g, and the amount of nickel acetate tetrahydrate added is 0.671 g, so that a composite transition bimetallic oxide catalyst (denoted as Co) with a theoretical mass distribution of 25% CoFe2O4 and 75% NiFe2O4 can be obtained. 0.25 Ni 0.75 Fe2O4).
[0059] The X-ray diffraction patterns of the magnetic composite transition bimetallic oxide catalysts prepared in Examples 1 to 5 are shown in the attached Figure 1As shown in the figure, it can be seen that the characteristic diffraction peaks appearing near 18.2°(111), 30.1°(220), 35.4°(311), 37.1°(222), 43.2°(400), 53.5°(422), 57.0°(511), 62.7°(440), 74.3°(620), 75.3°(533) and 79.1°(622) belong to NiFe2O4 with single-phase cubic spinel structure (JCPDS card No.54-0964). In addition, weak characteristic diffraction peaks were found near 43.1°(111), 51.4°(200) and 76.1°(220) and belong to Ni 0 Crystal (JCPDS card No. 04-0850). After adding cobalt salt to the initial raw material of NiFe2O4 synthesis, since both the generated CoFe2O4 and NiFe2O4 are single-phase cubic spinel structures, and the radius of Co atoms and Ni atoms are similar, the diffraction angle position of the characteristic diffraction peak of NiFe2O4 does not change, which also shows that the introduction of Co does not significantly destroy the crystal structure of NiFe2O4.
[0060] The SEM images, element distribution diagrams and H2-TPR curves of Example 1 and pure NiFe2O4 are shown in the attached figure. Figure 2 As shown in the figure, it can be seen that Co 0.20% Ni 0.80 Fe2O4 is in the form of nanoparticles with uniform size and no obvious agglomeration. Co, Ni, Fe and O elements are evenly distributed. Compared with pure NiFe2O4, the particle size is larger. 0.20 Ni 0.80 The reduction peaks of Fe2O4 at 412.0℃, 584.2℃ and 655.4℃ in the H2-TPR curve may be attributed to NiO x To you 0 Transformation, CoO x Transformed into Co 0 And Fe2O3 is reduced to Fe3O4, while pure NiFe2O4 only shows obvious FeO at 624.3℃ x Transformed into Fe 0 In addition, it can be further seen from the figure that Co 0.20% Ni 0.80 Fe2O4 has good stability at 350℃.
[0061] The X-ray photoelectron spectrum of the magnetic composite transition bimetallic oxide catalyst prepared in Example 1 is shown in the attached figure. Figure 3 As shown in the full XPS spectrum, it can be clearly observed that the catalyst contains four elements: Ni, Co, Fe and O. Two peaks at 710.6 eV and 723.6 eV are observed, which are attributed to Fe.3+ The binding energy peak of Ni 2p was observed in the range of 848-884 eV, of which the peaks near 855.0 and 872.6 eV were attributed to the surface NiO species, and two satellite peaks were observed near 860.9 and 878.9 eV. 0 The binding energy peak intensity is relatively weak; the Co 2p binding energy peak is observed in the range of 772-808eV, among which the binding peaks near 780.7 and 795.8eV are attributed to Co 2+ Two satellite energy spectrum peaks were also observed near 786.0 and 802.3 eV. These results confirm that the vast majority of Fe, Ni and Co species in the composite transition bimetallic oxide catalyst are Fe 3+ 、Ni 2+ and Co 2+ exists in the form of.
[0062] The NH3-TPD curve of the composite transition bimetallic oxide catalyst prepared in Example 1 is shown in the attached figure. Figure 4 As shown, it is generally believed that the desorption peak below 200°C corresponds to weak acid sites, the desorption peak in the temperature range of 200-400°C corresponds to medium-strong acid sites, and the desorption peak above 400°C is a strong acid site. Three desorption peaks can be obtained by fitting, which are 229.3, 423.9 and 512°C, respectively, which proves that the composite transition bimetallic oxide catalyst has strong acidity and more appropriately distributed weak acid sites, medium-strong acid sites and strong acid sites. Note: The actual scope of the present invention includes not only the specific embodiments disclosed above, but also all equivalent schemes for implementing or executing the present invention under the claims.
[0063] Example 6
[0064] A method for preparing a magnetic composite transition bimetallic oxide catalyst, the specific process is as follows:
[0065] S1. Add 0.179 g of cobalt acetate tetrahydrate, 0.716 g of nickel acetate tetrahydrate and 2.543 g of ferric acetylacetonate to 50 mL of deionized water, stir with a glass rod at room temperature and dissolve until ready for use;
[0066] S2. The mixed solution obtained in step S1 was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, 5 mL of hydrazine hydrate was added and shaken, and then the reactor was sealed and placed in a 150 ° C forced air drying oven for crystallization for 15 h;
[0067] S3. The hydrothermal reaction kettle in step S2 is taken out from the drying oven, and after it is naturally cooled to room temperature, the suspension in the kettle is centrifuged at a centrifugal speed of 5000 rpm for 5 minutes. The solid is then washed alternately with deionized water and anhydrous ethanol until it is neutral, and vacuum dried at 80°C for 4 hours to obtain a magnetic composite transition bimetallic oxide catalyst.
[0068] Example 7
[0069] A method for preparing a magnetic composite transition bimetallic oxide catalyst, the specific process is as follows:
[0070] S1. Add 0.179 g of cobalt acetate tetrahydrate, 0.716 g of nickel acetate tetrahydrate and 3.179 g of ferric acetylacetonate to 70 mL of deionized water, stir with a glass rod at room temperature and dissolve until ready for use;
[0071] S2. The mixed solution obtained in step S1 was transferred to a 100 mL polytetrafluoroethylene-lined hydrothermal reactor, 10 mL of hydrazine hydrate was added and shaken, and then the reactor was sealed and placed in a 100 ° C forced air drying oven for crystallization for 20 h;
[0072] S3. The hydrothermal reactor in step S2 is taken out from the drying oven, and after naturally cooling to room temperature, the suspension in the reactor is centrifuged at a centrifugal speed of 5000 rpm for 5 minutes. The solid is then washed alternately with deionized water and anhydrous ethanol until it is neutral, and vacuum dried at 90°C for 4 hours to obtain a magnetic composite transition bimetallic oxide catalyst.
[0073] Example 8
[0074] A method for preparing a magnetic composite transition bimetallic oxide catalyst, the specific process is as follows:
[0075] S1. Add 0.179 g of cobalt acetate tetrahydrate, 0.716 g of nickel acetate tetrahydrate and 3.814 g of ferric acetylacetonate to 30 mL of deionized water, stir with a glass rod at room temperature and dissolve until ready for use;
[0076] S2. The mixed solution obtained in step S1 was transferred to a 50 mL polytetrafluoroethylene-lined hydrothermal reactor, 3 mL of hydrazine hydrate was added and shaken, and then the reactor was sealed and placed in a 200 ° C forced air drying oven for crystallization for 10 h;
[0077] S3. The hydrothermal reactor in step S2 is taken out from the drying oven, and after naturally cooling to room temperature, the suspension in the reactor is centrifuged at a centrifugal speed of 5000 rpm for 5 minutes. The solid is then washed alternately with deionized water and anhydrous ethanol until it is neutral, and vacuum dried at 90°C for 4 hours to obtain a magnetic composite transition bimetallic oxide catalyst.
[0078] The catalysts prepared in Examples 1 to 5 were applied to the catalytic hydrogenation conversion reaction of lignite-related model compounds, and the catalyst activity and target product selectivity were evaluated by comparing the model compound conversion rate and the hydrogenation product yield. In addition, the ancient Dongming lignite from Inner Mongolia was used as the test object, and the comparison of the reaction products of non-catalytic hydrogenation conversion and catalytic hydrogenation conversion was used for explanation.
[0079] The following are two examples of applications of a magnetic composite transition bimetallic oxide catalyst.
[0080] Application Example 1
[0081] The magnetic Co prepared in Example 1 0.20 Ni 0.80 Fe2O4 nano-spherical catalyst is used in the catalytic hydrogenation reaction of Dongming lignite in Inner Mongolia. The specific application process is as follows:
[0082] (1) 0.5 g Co 0.20 Ni 0.80 Fe2O4 catalyst, 2 g of Inner Mongolia Dongming lignite and 20 mL of cyclohexane were added into a 100 mL autoclave;
[0083] (2) The air in the kettle was replaced with N2, and H2 was filled in so that the initial hydrogen pressure in the kettle was 1 MPa. The temperature was raised to 300°C at a heating rate of 10°C / min with a stirring speed of 200 rpm and kept at this temperature for 2 h;
[0084] (3) After cooling naturally to room temperature, the reaction mixture is quickly transferred to a Soxhlet extraction apparatus, and is thoroughly extracted with petroleum ether. The filtrate is collected and concentrated to obtain petroleum ether soluble matter, i.e., light components, and the light components are detected and analyzed;
[0085] (4) Subsequently, the petroleum ether insoluble matter is further extracted with an equal volume of acetone / carbon disulfide mixed solvent to obtain acetone / carbon disulfide mixed solvent soluble matter, i.e., a heavy component;
[0086] (5) Finally, the acetone / carbon disulfide insoluble matter was dried under vacuum at 40 °C for 12 h to remove the residual solvent, thereby obtaining coal residue.
[0087] In the above step (1), no Co is added. 0.20 Ni 0.80 Fe2O4 catalyst, other steps are the same as above, then the non-catalytic hydrogenation conversion reaction of Dongming lignite in Inner Mongolia can be carried out.
[0088] The yields of light components, heavy components and coal residues from catalytic hydrocracking and non-catalytic hydrocracking of Inner Mongolia Dongming lignite are calculated. Figure 5From the attached Figure 5 It can be seen that the introduction of magnetic Co 0.20 Ni 0.80 After the Fe2O4 nanosphere catalyst was added, the yield of the derived soluble matter increased from 12.23% to 15.37%. Among them, the yield of the light component increased from 4.12% to 6.23%, an increase of 51.2%, and the yield of the heavy component increased from 8.11% to 9.14%, an increase of 12.7%. The core group component distribution of the light component is shown in the attached figure. Figure 6 As shown in the figure, it can be further seen that the addition of Co 0.20 Ni 0.80 After adding Fe2O4 catalyst, the yield of alkanes in light components increased slightly, the yield of derived aromatics increased from 43.12% to 52.59%, an increase of 22.0%, while the yield of phenols decreased from 7.24% to 3.28%.
[0089] Application Example 2
[0090] The magnetic composite bimetallic oxide catalysts prepared in Examples 1 to 5 and pure NiFe2O4 were respectively applied to the catalytic hydrogenation conversion reaction of a lignite-related model compound (phenyl benzyl ether), and the specific application process is as follows:
[0091] (1) 50 mg of catalyst, 50 mg of phenyl benzyl ether and 20 mL of cyclohexane were added to an autoclave in sequence;
[0092] (2) After purging the reactor with high-pressure N2 three times to remove the air, H2 was injected into the reactor to make the initial H2 pressure (IHP) of the system reach the set value;
[0093] (3) heating the autoclave to a set temperature at a heating rate of 10°C / min with a stirring speed of 200 rpm and maintaining the temperature for a certain period of time;
[0094] (4) After the autoclave was cooled to room temperature naturally, the reaction mixture was taken out from the autoclave and filtered using a 0.22 μm organic filter head. The product composition and content of the obtained filtrate were analyzed by GC / MS.
[0095] When the IHP is 1MP, the reaction temperature is 300°C and the reaction time is 2h, the conversion rate and product yield of the catalytic hydrogenation reaction of phenyl benzyl ether by Examples 1 to 5 and pure NiFe2O4 are shown in Table 1.
[0096] Table 1
[0097]
[0098] The magnetic Co prepared in Example 1 0.20 Ni 0.80Fe2O4 nanosphere catalyst was used in the catalytic hydrogenation reaction of phenyl benzyl ether. The conversion rate and product distribution of phenyl benzyl ether changed with the initial hydrogen pressure, reaction temperature and reaction time as shown in Table 2.
[0099] Table 2
[0100]
[0101] It can be seen from Table 1 and Table 2 that under the same catalytic hydrogenation reaction conditions, the main products of phenyl benzyl ether catalytic hydrogenation cracking by several catalysts are aromatic hydrocarbons, especially benzene and toluene. In addition, there are more cyclohexane and methylcyclohexane in the products. 0.20 Ni 0.80 The molar yield of aromatic hydrocarbons in Fe2O4 hydrogenation cracking of phenyl benzyl ether is the highest (benzene: 34.7 mol%, toluene: 115 mol%). The yield of the main product aromatic hydrocarbons did not increase with the increase in the amount of cobalt salt added, but the yield of the hydrogenation product increased slightly. This shows that the composite transition bimetallic oxide catalyst has a certain ability to hydrogenate aromatic rings. First, Co 0.20 Ni 0.80 Fe2O4 catalyst can effectively activate H2 into H···H, and further split into H· and heterolytic H - Release H + , phenyl benzyl ether>C ar -O- is first attacked by H· to generate toluene and phenol. Toluene is converted into methylcyclohexane under the action of H···H, while phenol is converted into methylcyclohexane due to H + The attack dehydrates and converts to benzene, which is then converted to cyclohexane under the action of H···H. However, there may also be phenyl benzyl ether>C ar -CH2-O- is attacked by H· to generate benzene and benzyl alcohol, which is dehydrated to generate toluene. Benzene and toluene are reacted with H···H to generate cyclohexane and methylcyclohexane. Combined with the screening of reaction conditions, it can be seen that the increase in temperature is conducive to the dehydroxylation of phenol to produce benzene, and higher IHP may produce more H···H, which promotes the hydrogenation of aromatics to produce cycloalkanes.
[0102] The present invention prepares a magnetic CoFe2O4 and NiFe2O4 composite transition bimetallic oxide catalyst by a one-pot hydrothermal crystallization method. The method has a simple preparation process, a short production cycle, high safety and stability, no need for calcination, and is green and efficient. Compared with a single transition bimetallic oxide catalyst, the composite transition bimetallic oxide catalyst can provide more active sites and defect sites, and can efficiently and selectively cleave >CC< and heteroatom-containing >CX bridge bonds, thereby achieving the purpose of converting lignite-related model compounds and Inner Mongolia Dongming lignite into aromatic hydrocarbons with high yield.
[0103] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a magnetic composite transition bimetallic oxide catalyst, characterized in that: The steps include: S1. dissolving cobalt salt, nickel salt and iron salt in a solvent to obtain a mixed solution; S2. adding a strong reducing agent to the mixed solution, performing a hydrothermal reaction to crystallize to obtain a suspension; S3. Purify the suspension to obtain a magnetic composite transition bimetallic oxide catalyst.
2. The preparation method according to claim 1, characterized in that: The cobalt salt is at least one of cobalt acetate, cobalt sulfate or cobalt nitrate; The nickel salt is at least one of nickel acetate, nickel sulfate or nickel nitrate; The iron salt is at least one of ferric nitrate, ferric chloride or ferric acetylacetonate.
3. The preparation method according to claim 1, characterized in that: The volume ratio of the amount of cobalt salt, nickel salt and iron salt in S1 to the solvent is: mmol:mmol:mmol:mL=(0.18-0.9):(3.42-2.7):(7.2-10.8):(50-100). The preparation method according to claim 1, characterized in that the strong reducing agent is at least one of hydrazine hydrate or sodium borohydride.
4. The preparation method according to claim 1, characterized in that: The volume ratio of the strong reducing agent in S2 to the solvent in S1 is (5-20):
100.
5. The preparation method according to claim 1, characterized in that: The hydrothermal reaction temperature in S2 is 100-200°C, and the reaction time is 10-20h.
6. The preparation method according to claim 1, characterized in that: The purification in S3 is to obtain the magnetic composite transition bimetallic oxide catalyst by centrifuging, washing and drying the suspension.
7. The preparation method according to claim 6, characterized in that: The centrifugal speed is 4000-6000rpm, and the centrifugal time is 3-15min; the drying is vacuum drying, the drying temperature is 60-90°C, and the drying time is 4-20h.
8. A magnetic composite transition bimetallic oxide catalyst prepared according to the preparation method according to any one of claims 1 to 7.
9. Use of the magnetic composite transition bimetallic oxide catalyst according to claim 8 in lignite hydrogenation reaction.
10. Use of the magnetic composite transition bimetallic oxide catalyst according to claim 8 in the hydrogenation conversion reaction of lignite-related model compounds.